Diversity of mites associated with Raoiella indica (Acari: Prostigmata) on coconut palms in the central region of the Brazilian Amazonia, with emphasis on the predaceous Phytoseiidae (Acari: Mesostigmata) - Da Cruz, Wilton Pires [UNESP]; Krug, Cristiane; Nascimento De Vasconcelos, Geraldo Jose; De Moraes, Gilberto Jose (Systematic & Applied Acarology Soc London, Natural History Museum, 2015)
The mite Raoiella indica Hirst (Tenuipalpidae) has caused significant damage to coconut palms in the American continent and in the Caribbean area. Emphasis has been given to the establishment of sustainable measures for the control of this pest in this region, especially the use of predaceous mites. The objective of this study was to determine the occurrence of R. indica and other mites on coconut palms in Manaus (capital of the Amazonas state) and other three neighboring municipalities, at different periods of the year, with emphasis on mites of the family Phytoseiidae. Our hypothesis was that R. indica was not widespread in Manaus region, that it was found at low population levels and in association with a high diversity of predatory mites. Samples were collected at four periods, August/September 2012 (when rainfall was lower), November/December 2012 (beginning of the period of intense rainfall), February/March 2013 (period of intense rainfall) and May/June 2013 (beginning of the period with lower rainfall). Leaflets, fruits and flowers were sampled from ten plants at each sampling site (one from each municipality) and at each sampling period. Most mites were found on leaflets; 73.9% of these were predominantly phytophagous, 6.1% predominantly predaceous and 20.0% had mainly other feeding habits. Eriophyoidea, tarsonemids and tetranychids were the most abundant groups of predominantly phytophagous mites. Raoiella indica was found at low population levels and in a single site (Iranduba). Phytoseiids were by far the predominant predators (42.5% of the predaceous mites); they were most abundant during intense rainfall. Amblyseius aerialis (Muma), Euseius alatus De Leon and Amblydromalus sp. nov. were the most abundant predators of this family. Cunaxid mites accounted for 27.2% of the predaceous mites. The results of this study suggested that R. indica was not widespread in the region, that it was found at low population levels and that a great diversity of predaceous mites was found on coconut plants in that region. It remains to be seen whether these would be able to maintain the population of that pest under control.